Human investment and its role in achieving organizational effectiveness within the sports administration The Directorate of Youth and Sports of the State of msila model - بن البار سعيد (sports creativity, 2025)
RÉSUMÉ : Due to the great interest in the human element in all fields by all international organizations and organizations, this study aims to determine whether the skills and knowledge acquired by the human element have a role in achieving organizational effectiveness within the sports administration at the Directorate of Youth and Sports of the State of MSILA. Which expresses the social phenomenon and as Abidat knows that he is interested in analyzing the phenomenon in question and highlights the importance of the method and the expression of quantitative and qualitative analysis analytically highlights the relationship between variables The research community in this study In all the managers and employees of the Directorate of Youth and Sports in the state of msila divided into four interests, namely the Department of Physical Education and Sports, the Youth Activities Department, the Investment and Equipment Department, the Training Department and the Means Department. In this study, we relied on the comprehensive survey method after deleting the survey sample which was 5 employees. This is due to the fact that the administrative number of the Directorate of Youth and Sports in the State of msila is low and estimated at 35 employees. During the distribution of the form to all those within the Directorate and thus obtain the results represent the community as a whole has been adopted through the theoretical research and previous studies, we designed a questionnaire consisting of 18 questions distributed on three axes, after it was presented to the arbitrators and then modified the terms of this form on the contrary Language of some items have been adjusted. The study concluded that education programs must be allocated in the sports departments to create positive motives for participation in the educational programs of the employees, with the suitability of the educational programs for training and the needs of the labor market, in addition to conducting training and training courses for the employees in these institutions, taking into consideration the effectiveness of the training programs and programs. Workers and employees, while improving the salaries of workers to achieve effectiveness within the organization, and to give importance to the moral incentives which are a means to achieve improvement of this organizational effectiveness on the one hand, and on the other hand the employees of the sports departments to have doctrines Face Slokathm to positive organizational effectiveness and development of self-interest in the task of knowledge to them